2015
DOI: 10.1186/s13104-015-1495-z
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and treatment outcome of hyperglycemic emergencies at Jimma University Specialized Hospital, southwest Ethiopia

Abstract: BackgroundDiabetic ketoacidosis (DKA) and hyperosmolar hyperglycemic state (HHS) commonly known as hyperglycemic emergencies are the two most common life-threatening acute metabolic complications of diabetes. The objective of this study is to assess predictors and treatment outcome of hyperglycemic emergencies (HEs) among diabetic patients admitted to Jimma University Specialized Hospital (JUSH).MethodsIt is a three year retrospective review of medical records of patients admitted with HEs at JUSH. Patient dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
55
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(76 citation statements)
references
References 31 publications
14
55
6
Order By: Relevance
“…HHS was the major HE case. This nding goes in line with studies from Nigeria and Taiwan (15,(24)(25)(26)(27) but stands against a study reported that DKA was the commonest HE (22). The higher prevalence of HHS in our study might be explained by the fact that the majority of the study participants were T2DM patients, and that HHS often raids patients with uncontrolled T2DM (28).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…HHS was the major HE case. This nding goes in line with studies from Nigeria and Taiwan (15,(24)(25)(26)(27) but stands against a study reported that DKA was the commonest HE (22). The higher prevalence of HHS in our study might be explained by the fact that the majority of the study participants were T2DM patients, and that HHS often raids patients with uncontrolled T2DM (28).…”
Section: Discussionsupporting
confidence: 90%
“…The rate of comorbidity in our study was 32.4%. This rate is higher than the 22.1% reported by a study from Jimma (22). The relatively higher proportion of known DM patients in our study might justify this higher prevalence of comorbidity.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…In Ethiopia, mortality from hyperglycemic emergencies is not well documented but comparatively high in few studies. A study done in Jimma found a mortality rate of 9.8 % from hyperglycemic emergencies (12).Socioeconomic factors, particularly the cost and unreliability of insulin supplies are the major obstacles to the control of diabetes and prevention of ketoacidosis in Ethiopian patients (13). Mortality rate is lower in patients that received appropriate treatment and management of precipitating factors (14).…”
Section: Introductionmentioning
confidence: 99%